Data for Temporal and spatial variability of ammonia in urban and agricultural regions of northern Colorado, United States - Li, Yi; Thompson, Tammy M.; Van Damme, Martin; Chen, Xi; Benedict, Katherine B.; Shao, Yixing; Day, Derek; Boris, Alexandra; Sullivan, Amy P.; Ham, Jay; Whitburn, Simon; Clarisse, Lieven; et al. (Colorado State University. Libraries, 2017)
Concentrated agricultural activities and animal feeding operations in the northeastern plains of Colorado represent an important source of atmospheric ammonia (NH3) that contributes to regional fine particle formation and to nitrogen deposition to sensitive ecosystems in Rocky Mountain National Park (RMNP) located ~ 80 km to the west. In order to better understand temporal and spatial differences in NH3 concentrations in this source region, weekly concentrations of NH3 were measured at 14 locations during the summers of 2010 to 2015 using Radiello passive NH3 samplers. Weekly (biweekly in 2015) average NH3 concentrations ranged from 2.66 μg/m3 to 42.7 μg/m3 with the highest concentrations near large concentrated animal feeding operations (CAFOs). The annual summertime mean NH3 concentrations were stable in this region from 2010 to 2015, providing a baseline against which concentration changes associated with future changes in regional NH3 emissions can be assessed. Vertical profiles of NH3 were also measured on the 300 m Boulder Atmospheric Observatory (BAO) tower throughout 2012. The highest NH3 concentration along the vertical profile was always observed at the 10 m height (annual average concentration of 4.63 μg/m3), decreasing toward the surface (4.35 μg/m3) and toward higher altitudes (1.93 μg/m3). Seasonal changes in the steepness of the vertical concentration gradient were observed, with the sharpest gradients in cooler seasons when thermal inversions restricted vertical mixing of surface-based emissions. The NH3 spatial distributions measured using the passive samplers are compared with NH3 columns retrieved by the Infrared Atmospheric Sounding Interferometer (IASI) satellite and concentrations simulated by the Comprehensive Air quality Model with extensions (CAMx), providing insight into the regional performance of each. The satellite comparison adds to a growing body of evidence that IASI column retrievals of NH3 provide very useful insight into regional variability in atmospheric NH3, in this case even in a region with strong local sources and sharp spatial gradients. The CAMx comparison indicates that the model does a reasonable job simulating NH3 concentrations near sources but tends to underpredict concentrations at locations farther downwind. Excess NH3 deposition by the model is hypothesized as a possible explanation for this trend.
Department of Atmospheric Science